A Billion-Year Facelift and Cleaner Air. (2001) - Unknown
Abstract : Science leads the first (or is it second?) year of the millennium with a story about a facelift for Jupiters moon, Ganymede. Nature leads with a story about new regulations on diesel-powered vehicles in the U.S.